Private Equity Financing in Zambia: Determinants and Constraints - Lumbala, Malasa (Graduate School of Business (GSB), 2019)
Growth and development of small and medium-sized enterprises (SMEs) are the key drivers of economic growth and development in Africa. While this has become a widely accepted idea, access to financing for growth remains a stumbling block for many enterprises in Zambia. Traditional lenders (i.e. banks) are risk averse because they may not understand the SME market and have been negatively impacted by information asymmetry that is often associated with these ventures. As a result, they tend to charge exorbitant interest rates that are unsustainable for long-term growth. The existing focus of many microfinance institutions in Zambia is typically directed towards salaried employees which crowds out lending to SMEs. Private equity financing, on the other hand, presents an alternative solution to the long-term financing dilemma faced by enterprises. The Zambian private equity market is itself in a nascent space but shows much potential. This dissertation seeks to determine what drives private equity financing in Zambia and what constrains it. The dissertation adopts a qualitative research approach relying on the interviews of various Fund Managers who are familiar with investing in Zambia. The paper finds that private equity investment in Zambia is determined and catalysed broadly by business attractiveness and the business environment. Business attractiveness is underpinned by management capacity, the business track record, exits and returns, impact potential and business scalability. The business environment is driven by political stability, GDP growth and population growth. The sector is however, constrained by a less developed private equity culture, limited opportunities to invest and currency risk.